Dc-dc 3ssc-a-based boost converter: Analysis, design, and experimental validation - Souza, Lucas Carvalho [UNESP]; Morais, Douglas Carvalho [UNESP]; da Costa e Silva, Luciano de Souza; de Seixas, Falcondes José Mendes [UNESP]; Arenas, Luis De Oro [UNESP] (MDPI, 2021)
A detailed analysis and validation of the DC-DC boost converter based on the three-state switching cell (3SSC) type-A are presented in this paper. The study of this topology is justified by the small amount of research that employs 3SSC-A and the advantages inherent to 3SSC-based converters, such as the division of current stresses between the semiconductors, the distribution of thermal losses, and the high-density power. Therefore, a complete static analysis of the converter is described, as well as the study of all voltage and current stresses in the semiconductors, the development of a loss model in all components, and a comparison with other step-up structures. Additionally, the small-signal model validation is accomplished by comparing the theoretical frequency response and the simulated AC sweep analysis. Finally, implementing a simple controller structure, the converter is experimentally validated through a 600 W prototype, where its overall efficiency is examined for various load conditions, reaching 96.8% at nominal load.
Keywords: 3SSC type-A; Boost converter; DC-DC converter; Right-half-plane (RHP) zero; Three-state switching cell (3SSC)